MENINGKATKAN HASIL BELAJAR PESERTA DIDIK MELALUI PENDEKATAN TEACHING AT THE RIGHT LEVEL BERBANTUAN LKPD PADA MATA PELAJARAN MATEMATIKA KELAS 2-B DI SDN BONDONGAN - Elis Nurul Huda; Fitri Siti Sundari; Siti Nurjanah (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
This research was conducted at SDN Bondongan in Bogor City, where students have been experiencing difficulties in learning mathematics, resulting in the failure to achieve the planned learning objectives. This study aims to provide solutions to the problems faced by the students in class 2-B at SDN Bondongan, with the goal of improving their learning outcomes through the Teaching at the Right Level approach using the Problem-Based Learning model assisted by LKPD (Lembar Kerja Peserta Didik) in the mathematics subject for class 2-B at SDN Bondongan for the 2023/2024 academic year. The results showed that after implementing the Teaching at the Right Level approach with the Problem-Based Learning model assisted by LKPD in the mathematics subject for class 2-B at SDN Bondongan, there was an average increase of 16% in the learning outcomes of the students in class 2-B at SDN Bondongan in Bogor City in mathematics. Penelitian ini dilakukan di SDN Bondongan Kota Bogor, di sekolah tersebut terdapat permasalahan yang dirasakan oleh peserta didik dalam mempelajari mata pelajaran matematika, mengakibatkan tidak tercapainya tujuan pembelajraan yang telah dirancang. Penelitian ini berupaya memberikan solusi terhadap permasalahan yang dihadapi di kelas 2-B SDN Bondongan dengan tujuan untuk meningkatkan hasil belajar peserta didik melalui pendekatan Teaching at The Right Level dengan model pembelajaran Problem Based Learning berbantuan LKPD (Lembar Kerja Peserta Didik) pada mata pelajaran matematika kelas 2-B di SDN Bondongan Tahun Pelajaran 2023/2024. Hasil penelitian menunjukan bahwa setelah diterapkannya pendekatan pendekatan Teaching at The Right Level dengan model pembelajaran Problem Based Learning berbantuan LKPD pada mata pelajaran matematika kelas 2-B di SDN Bondongan dapat meningkatkan rata-rata 16% hasil belajar peserta didik kelas 2-B SDN Bodongan Kota Bogor dalam mata pelajaran matematika.